Glucose to Complications: Understanding Secondary Effects in Diabetes Mellitus - P. K. Prabhakar (Sumatera Medical Journal, 2024)
Background: Diabetes Mellitus (DM) is a complex metabolic disorder characterized by persistent hyperglycemia, impacting millions globally. While glucose control is central to its management, understanding secondary complications is crucial for comprehensive care. Objective: This paper explores the intricate relationship "From Glucose to Complications" in DM, elucidating the pathophysiological mechanisms and organ system involvement. Methods: This paper emphasizes preventive strategies and holistic management approaches to mitigate complications. Results: Microvascular complications encompass diabetic retinopathy, nephropathy, and neuropathy, each posing significant morbidity and mortality risks. Macrovascular complications, including atherosclerosis and stroke, contribute substantially to cardiovascular morbidity in diabetic individuals. Metabolic derangements such as dyslipidemia and obesity further exacerbate the risk profile. Endocrine disturbances, neurological sequelae, and cognitive impairments represent additional burdens in DM management. Conclusion: effective management of Diabetes Mellitus (DM) and its associated complications necessitates a multifaceted approach encompassing glycemic control, lifestyle interventions, and pharmacological therapies.